The scope of taxation of income from illegal activities in selected common law jurisdictions - Hingun, Mohsin; Nafiu, Olaitan S. (International Islamic University Malaysia, 2015)
The taxation of income from illegal activities is well established in several common law jurisdictions. In the broader sense income or profits from a trade, profession or vocation irrespective of the issue of legality will be taxable. The courts have drawn a distinction between cases where normal income producing activities become illegal due to non-compliance with licensing requirements or acting in contravention to a ban in trading on one hand and profits acquired as a result of the commission of systematic crimes such as burglary on the other hand. Income from the latter source is not taxable. The objective of this paper is to argue against such a distinction, to highlight the problems inherent in computing income from an illegal source and to examine the difficulties in formulating rules governing the deductibility of expenditures incurred in earning income from illegal activities